Hubungan Antara Successfull Aging Dan Penyesuaian Diri Lanjut Usia Dengan Penerimaan Diri - Ulfah, Khoiriya; Thoha, Annisa Fatin; Qohar, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research begins with the thought that successful aging and adjustment have a relationship with self-acceptance in elderly individuals. The purpose of this study was to determine the relationship between successfull aging and self-adjustment with the self-acceptance of retired member organizations (PWRI) of Lampung Province. The hypothesis proposed in this study is that there is a relationship between successfull aging and old age adjustment and self-acceptance.The population in this study were members of the Republic of Indonesia Wredatama Association (PWRI) Lampung Ranting I Kedaton, Bandar Lampung city. The sampling method for this research is to use population techniques that refer to Suharsimi Arikunto's theory, that if the subject is less than 100 people, it is better to take all so that the research is a population study. The sample taken in this study were all PWRI members who held monthly meetings at the PWRI meeting hall on Landak street No. 1 Kedaton, Bandar Lampung city. The sample in this study was obtained as many as 60 members of the Republic of Indonesia Wredatama Pensioners (PWRI).The data collection method uses three scales namely self-acceptance scale, successfull aging scale and adjustment scale with likert scale model. Data collected were analyzed by two predictor regression tests with the help of SPSS 16.0 for windows.Based on the results of the data analysis above, it means that the proposed hypothesis can be accepted and it can be concluded that there is a relationship between successfull aging and adjustment of old age with self-acceptance in retirees.